2011
DOI: 10.3113/fai.2011.0473
|View full text |Cite
|
Sign up to set email alerts
|

STAR™ Ankle: Long-Term Results

Abstract: The first U.S. prospective long-term survivorship data with the STAR™ Ankle prosthesis found it to be an excellent long-term option for the treatment of ankle arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
132
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 36 publications
14
132
1
3
Order By: Relevance
“…Ankle replacements have only recently been added to the UK's National Joint Registry; however, series of data from the United Kingdom (65,70) and United States (71), and joint registry data from the Finnish (72), Swedish (68), and New Zealand (73) arthroplasty registers are available. A systematic review of registry data in 2013 showed that only 6 countries routinely collected total ankle arthroplasty data for their national joint replacement registries (74).…”
Section: Joint Sacrificing Surgerymentioning
confidence: 99%
“…Ankle replacements have only recently been added to the UK's National Joint Registry; however, series of data from the United Kingdom (65,70) and United States (71), and joint registry data from the Finnish (72), Swedish (68), and New Zealand (73) arthroplasty registers are available. A systematic review of registry data in 2013 showed that only 6 countries routinely collected total ankle arthroplasty data for their national joint replacement registries (74).…”
Section: Joint Sacrificing Surgerymentioning
confidence: 99%
“…Most promising, in 2011, Mann et al (11) demonstrated implant survival rates of 96% at 5 years and 90% at 10 years, with significant improvements in the American Orthopaedic Foot and Ankle Society ankle-hindfoot scores and pain scores. Considering these encouraging results, Mann et al (11) described TAR as an "excellent long-term option for treatment of ankle arthritis." In 2010, a prospective multicenter trial was conducted comparing arthrodesis and arthroplasty, with a mean follow-up of 4 years (15).…”
mentioning
confidence: 94%
“…To improve the survivorship of these advanced TAR systems, implants were designed to more closely mimic normal ankle anatomy and kinematics (9)(10)(11)(12)(13)(14). Most promising, in 2011, Mann et al (11) demonstrated implant survival rates of 96% at 5 years and 90% at 10 years, with significant improvements in the American Orthopaedic Foot and Ankle Society ankle-hindfoot scores and pain scores.…”
mentioning
confidence: 98%
“…An estimated 50,000 Americans experience end-stage ankle arthritis every year [1]. Although ankle arthrodesis has historically been the ''gold standard'' treatment option for managing recalcitrant ankle arthritis, encouraging mid to longterm data following third generation TAR has made arthroplasty a viable option to arthrodesis [2][3][4][5][6][7]. The utility of ankle arthroplasty has advanced dramatically over the past 20 years, ushered in by improvements in surgical technique, implant design, material geometry, and instrumentation.…”
Section: Introductionmentioning
confidence: 99%